2020
DOI: 10.1080/19490976.2020.1840764
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the bacterial gut microbiota during controlled human infection with Necator americanus larvae

Abstract: Hookworms are soil-transmitted helminths that use immune-evasive strategies to persist in the human duodenum where they are responsible for anemia and protein loss. Given their location and immune regulatory effects, hookworms likely impact the bacterial microbiota. However, microbiota studies struggle to deconvolute the effect of hookworms from confounders such as coinfections and malnutrition. We thus used an experimental human hookworm infection model to explore temporal changes in the gut microbiota before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Nematode presence (strongylid nematodes, Strongyloides ) was also associated with lower bacterial richness in red colobus, but in PF. Although studies of the interactions between helminths and microbiota in wild animal populations are still relatively new, we speculate that the discrepancy found here may derive from a temporary instability in microbiota composition as a result of helminth infections which may recover over time, as already found in humans under controlled settings 17 . Further longitudinal studies on the same wild populations could help to fulfil this gap and reveal the actual influence of each gut component over time.…”
Section: Discussionmentioning
confidence: 50%
“…Nematode presence (strongylid nematodes, Strongyloides ) was also associated with lower bacterial richness in red colobus, but in PF. Although studies of the interactions between helminths and microbiota in wild animal populations are still relatively new, we speculate that the discrepancy found here may derive from a temporary instability in microbiota composition as a result of helminth infections which may recover over time, as already found in humans under controlled settings 17 . Further longitudinal studies on the same wild populations could help to fulfil this gap and reveal the actual influence of each gut component over time.…”
Section: Discussionmentioning
confidence: 50%
“…(2014) found that experimental administration of N. americanus to healthy individuals did not affect fecal microbiota, but they did not reject the possibility of having minor changes to microbiota at the site of infection. Ducarmon et al (2020) showed an increase in the species richness of the gut microbiota among all volunteers during an established infection, but the diversity and stability were almost unchanged. Even the group with many symptoms was characterized by transient microbiota instability and subsequent recovery.…”
Section: Ancylostomiasismentioning
confidence: 94%
“…A study on 8 healthy volunteers infected with 20 L3 larvae found no major impact on the gut microbiota at 8 weeks post infection 167 . A more recent study on 20 healthy young volunteers with higher dosages (i.e., 50, 100, or 150) of L3 found that the bacterial richness increased significantly during the established infection phase (week 8-20), but not during the acute infection phase (trial week 0-8) 168 . As hookworm resides in the small intestine, these results are consistent with deworming studies indicating that these worms may not alter the gut microbiota significantly, especially in the first 8 weeks after the infection.…”
Section: Effects Of Helminths On Microbiome During Challenge Infectionmentioning
confidence: 95%
“…Controlled experimental challenge infections may be an approach to minimize confounding factors and determine more direct effects of helminths on the microbiome and mucosal responses. The hookworm, N. americanus infection studies have been conducted on healthy individuals 167,168 , participants with relapsing multiple sclerosis 169 , and coeliac disease 170 . A study on 8 healthy volunteers infected with 20 L3 larvae found no major impact on the gut microbiota at 8 weeks post infection 167 .…”
Section: Effects Of Helminths On Microbiome During Challenge Infectionmentioning
confidence: 99%